2010
DOI: 10.1007/s13197-010-0105-2
|View full text |Cite
|
Sign up to set email alerts
|

Development of ready-to-eat appetisers based on pepper and their quality evaluation

Abstract: Appetiser is a need based product for defence forces deployed at high altitudes. Ready to eat appetisers in the form of munches i.e. pepper munch and lemon munch were developed by using response surface methodology and central composite rotatable design with active ingredients as variables and quality parameters such as acidity, sugars and sensory acceptability score as responses. The ingredients like raisins and dates were pre-processed by frying in ghee (butter oil) while juice was extracted from pseudolemon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Many researchers have found honey to be a suitable alternative for healing wounds and burns, and for oral health (Lay-Flurrie 2008;Molan 2001b). Honey is also a highly valuable ingredient in foods (Bath and Singh 2001;Naveena et al 2007;Kotoki and Deka 2010;Wadikar et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have found honey to be a suitable alternative for healing wounds and burns, and for oral health (Lay-Flurrie 2008;Molan 2001b). Honey is also a highly valuable ingredient in foods (Bath and Singh 2001;Naveena et al 2007;Kotoki and Deka 2010;Wadikar et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…b 0 is constant coefficient of intercept, b 1 -b 5 are constant coefficients of linear terms, b6-b10 are constant coefficients of quadratic terms and b11-b20 are constant coefficients of interaction terms, respectively, and X 1 -X 5 are independent variables (Te, t, Sr, En and S). Response surface methodology (RSM) method was followed according to different literatures where RSM was used for optimization (Alam et al 2010;Chakraborty et al 2011;Garg and Singh 2010;Wadikar et al 2010;Modha and Pal 2011;Xu et al 1998).…”
Section: Response Surface Methodology (Rsm)mentioning
confidence: 99%
“…Popping of conditioned pearl millet using heated sand (250 ºC) resulted with yield and expansion ratio of popped grains ranging from 8.3-77.1% and 2.3-11.3% respectively [7]. Puffing process reduces phytic acid (21-50 %) and tannins (3-18 %) [16] whereas popping significantly increases bio-accessibility of Zn (18 g/100 g) in native millet [3].The varietal effect of finger millet on puffing quality shown that brown seeded varieties are more suitable for puffing whereas white seeded varieties yielded organoleptically superior quality puff [17]. The brown seeded variety 'PR 202' gave the maximum puffing yield followed by 'JNR 852'with medium expansion.…”
Section: Austin Publishing Groupmentioning
confidence: 99%